Functional Relationships Between Fertility and Some Soil Parameters - EKBERLI*, IMANVERDI; KERIMOVA†, ELLADA (Asian Journal of Chemistry, 2010)
The importance of empirical and theoretical model derivationin agriculture has been increased due to presence of overwhelmingdata obtained from researches in soil science and extensive usageof computer in Agriculture. Mathematical definition of fertility issignificantly related to research of ecological fertility, usage ofmaximum parameter values, management and prediction of fertility.The derivation of mathematical models and their application afterexecution of field and laboratory studies are important steps incomprehending soil fertility. Some agroecological, agrophysicaland agrochemical characteristics of soils that constitute conceptualsoil model are taken into account in the field and laboratorystudies in order to obtain fertility model for irrigated gray-meadowsoils. These parameters were determined, evaluated and studiedbased on the field experiments. The relationships between theparameters and productivity of cotton were found out and staticmodels were derived by using the least square methods. Thecorrelation coefficients (average R = 0.90) of these models withmultiple parameters came out to be statistically significant. Theextreme points of function were calculated in order to obtainmaximum level of the product cultivation in theoretical way. Theevaluation of fertility level of experimental soils by these empiricalmodels seems to be possible as well.